Investigating the social world : the process and practice of research - Schutt, Russell K. (Thousand Oaks, Calif. : Sage Publications, 2012)
"A comprehensive, balanced text text for Research Methods courses found in Sociology, Communication/Journalism, Political Science, Public Administration, and other social science disciplines. It is used in undergraduate through graduate level courses"--Provided by publisher.
Science, society, and social research -- The process and problems of social research -- Research ethics and philosophies -- Conceptualization and measurement -- Sampling -- Research design and causation -- Experiments -- Survey research -- Qualitative methods -- Qualitative data analysis -- Evaluation and policy research -- Historical and comparative research -- Secondary data analysis and content analysis -- Quantitative data analysis -- Summarizing and reporting research -- Appendix A: Questions to ask about a research article -- Appendix B: How to read a research article -- Appendix C: Table of random numbers.
Includes bibliographical references and index.
Keywords: Social problems -- Research; Social sciences -- Research